Exploring mechanisms of skin aging: insights for clinical treatment - Zhang, Meiqi; Huang, Xuewen; Zhou, Shuwei; Wang, Siyu; Zhou, Yan; Han, Xuan (Frontiers in Immunology, 2024)
The skin is the largest organ in the human body and is made up of various cells and structures. Over time, the skin will age, which is not only influenced by internal factors, but also by external environmental factors, especially ultraviolet radiation. Aging causes immune system weakening in the elderly, which makes them more susceptible to dermatosis, such as type 2 inflammatory mediated pruritus. The immune response in this condition is marked by senescent cells consistently releasing low amounts of pro-inflammatory cytokines through a senescence-associated secretory phenotype (SASP). This continuous inflammation may accelerate immune system aging and establish a connection between immune aging and type 2 inflammatory skin diseases. In addition, two chronic pigmentation disorders, vitiligo and chloasma, are also associated with skin aging. Aged cells escape the immune system and accumulate in tissues, forming a microenvironment that promotes cancer. At the same time, “photoaging” caused by excessive exposure to ultraviolet radiation is also an important cause of skin cancer. This manuscript describes the possible links between skin aging and type 2 inflammation, chronic pigmentation disorders, and skin cancer and suggests some treatment options.